2022
DOI: 10.1371/journal.pone.0266406
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy and possible mechanism of action of 2-hydroxyisocaproic acid (HICA)

Abstract: The exploitation of natural antimicrobial compounds that can be used in food preservation has been fast tracked by the development of antimicrobial resistance to existing antimicrobials and the increasing consumer demand for natural food preservatives. 2-hydroxyisocaproic acid (HICA) is a natural compound produced through the leucine degradation pathway and is produced in humans and by certain microorganisms such as lactic acid bacteria and Clostridium species. The present study investigated the antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“… 28 2-Hydroxyisocaproic acid is produced through the leucine degradation pathway, and it was effective in inhibiting the growth of tested Gram-positive and Gram-negative bacteria. 29 HICA was not detected in the initial stage of kimchi fermentation. However, it was detected at a level of 0.241 mMol in the 1st week and detected approximately twice as much in the 2nd week at 0.486 mMol.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“… 28 2-Hydroxyisocaproic acid is produced through the leucine degradation pathway, and it was effective in inhibiting the growth of tested Gram-positive and Gram-negative bacteria. 29 HICA was not detected in the initial stage of kimchi fermentation. However, it was detected at a level of 0.241 mMol in the 1st week and detected approximately twice as much in the 2nd week at 0.486 mMol.…”
Section: Resultsmentioning
confidence: 78%
“…2-Hydroxyisocaproic acid and 3-phenyl lactic acid are known to be functional substances produced via the LAB metabolism of kimchi . 2-Hydroxyisocaproic acid is produced through the leucine degradation pathway, and it was effective in inhibiting the growth of tested Gram-positive and Gram-negative bacteria . HICA was not detected in the initial stage of kimchi fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have found that high concentrations of valine, leucine, and isoleucine are correlated with a high prevalence of lactobacilli in healthy pregnant women ( 101 , 102 ). Interestingly, our study indicated that, relative to mock-inoculated controls, all lactobacilli produced levated levels of branched-chain amino acids or related metabolites, such as 2-hydroxy-3-methylvalerate and alpha-hydroxyisocaproate, which are putative antimicrobial properties ( 103 ). Others have observed metabolites such as glycerophospholipids being positively correlated with Lactobacillus abundance ( 104 ).…”
Section: Discussionmentioning
confidence: 91%
“…All compounds are listed in decreasing order of signal intensity. The highest compounds identified in negative ionization mode were the quinoxalines xanthurenic acid and kynurenic acid, along with the phenyllactic and leucinic acids (Table 6), two important antimicrobial compounds [36,37]. The highest compounds identified in positive ionization mode were tricin 7-rhamnosyl-(1->2)-galacturonide, a tricin derivative, two isomers of 6-hydroxyluteolin 6,4 -dimethyl ether 7-rutinoside, and the vitamin riboflavin (Table 7).…”
Section: Process Assessmentmentioning
confidence: 99%
“…Besides the high antioxidant activity of the final extract, antimicrobial activity could have also possibly been attained by the presence of specific organic acids such as phenyllactic and leucinic acids [36,37]. In the same way, the amino acids and peptides present play important roles in action as antimicrobial, antithrombotic, antihypertensive, opioid, immunomodulatory, antioxidant, and mineral binding agents [39].…”
Section: Antioxidant Capacitymentioning
confidence: 99%